2020
DOI: 10.1093/jisesa/ieaa126
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward an Attract-and-Kill Device for Asian Citrus Psyllid (Hemiptera: Liviidae) Using Volatile Signatures of Citrus Infected With Huanglongbing as the Attractant

Abstract: Asian citrus psyllid, Diaphorina citri (Kuwayama), preferentially orient toward citrus hosts infected with the phytopathogenic bacterium, Candidatus liberibacter asiaticus (CLas) the agent of citrus greening (Huanglongbing, HLB), compared to uninfected counterparts. We investigated whether this preference for the odors of infected plants could be useful for the development of an attract-and-kill (AK) device for D. citri. Twenty-nine blends of volatile organic compounds derived from the odor of citrus infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
(49 reference statements)
0
18
0
1
Order By: Relevance
“…Identifying an effective attractant for D. citri can enhance the effectiveness of pesticide managements against this pest and is a prerequisite for developing an attract-and-kill system for the control of D. citri. 37 Many volatiles including linalool, limonene, ⊎-caryophyllene and methyl salicylate have been identified from host plants and have been shown to be attractive to D. citri. 20,21,23,25 For example, an attractant blend of tricosane, geranial, methyl salicylate, geranyl acetone, linalool, phenylacetaldehyde, (E)-⊎-ocimene co-formulated with spinosad insecticide effectively reduced D. citri population density by up to 84% in a small citrus orchard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying an effective attractant for D. citri can enhance the effectiveness of pesticide managements against this pest and is a prerequisite for developing an attract-and-kill system for the control of D. citri. 37 Many volatiles including linalool, limonene, ⊎-caryophyllene and methyl salicylate have been identified from host plants and have been shown to be attractive to D. citri. 20,21,23,25 For example, an attractant blend of tricosane, geranial, methyl salicylate, geranyl acetone, linalool, phenylacetaldehyde, (E)-⊎-ocimene co-formulated with spinosad insecticide effectively reduced D. citri population density by up to 84% in a small citrus orchard.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,23,25 For example, an attractant blend of tricosane, geranial, methyl salicylate, geranyl acetone, linalool, phenylacetaldehyde, (E)-⊎-ocimene co-formulated with spinosad insecticide effectively reduced D. citri population density by up to 84% in a small citrus orchard. 37 Numerous host plant volatiles have been used to detect D. citri electrophysiological responses via single sensillum recordings and an attractant blend of myrcene, ethyl butyrate and p-mycene slightly improved field attraction of D. citri to yellow traps. 38 These findings indicate that host plant volatiles have great potential for use as attractants for D. citri.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations to find optimum pull plants is active as well (Beloti et al 2017;Tomaseto et al 2016). Attractant lures, as for example those based on pheromones or host volatile cues, are also being investigated to increase captures in trapping devices, which may also contribute to the pull side of the strategy (Martini et al 2020;Zanardi et al 2019).…”
Section: Figurementioning
confidence: 99%
“…Efforts are currently underway to evaluate various blends to achieve the same. Recently, (Martini et al 2020) evaluated a multi-component blend composed of Dichloromethane, tricosane, geranial, methyl salicylate, geranyl acetone, 1-tetradecene, linalool, phenylacetaldehyde, (E)-beta-ocimene, dichloromethane and concluded that a formulation of this incorporating Spinosad may be effective in attracting and kill as a management option for D. citri. Also, other blends of terpenes have been evaluated for their efficacy in the management of particularly the African Triozid T. erytreae (Antwi-Agyakwa et al 2019).…”
Section: Use Of Semiochemicalsmentioning
confidence: 99%